2009
DOI: 10.1210/jc.2009-0096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resistance to Thyroid Hormone on the Cardiovascular System in Adults

Abstract: Our results suggest the presence of cardiovascular alterations in asymptomatic and untreated RTH patients similar to those reported in hypothyroid patients. Our strict selection likely created a bias in the inclusion of a particular type of RTH patients, who could represent a minority of patients with RTH. However, no correlation was found between the type of mutation and cardiovascular characteristics of RTH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In asymptomatic patients, Pulcrano et al, although, report the presence of echocardiographic signs similar to those reported in hypothyroid patients [ 20 ].…”
Section: Discussionmentioning
confidence: 57%
“…In asymptomatic patients, Pulcrano et al, although, report the presence of echocardiographic signs similar to those reported in hypothyroid patients [ 20 ].…”
Section: Discussionmentioning
confidence: 57%
“…In our cases, the cardiac symptoms could only be relieved by the combination of carbimazole and propranolol. Electrocardiogram and echocardiography every 2–3 years were recommended in symptomatic patients [ 13 ]. However, in our experience, regular electrocardiograms and echocardiography should be performed in older patients without any symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested an increased incidence of mitral valve prolapse among RTH β subjects. Finally, a reduced whole-body insulin sensitivity and dyslipidemia have been documented in a number of patients, suggesting an increased cardiovascular risk in RTH β (Kahaly et al 2002 ;Pulcrano et al 2009 ;Owen et al 2009 ).…”
Section: Cardiovascular Symptomsmentioning
confidence: 99%